2022
DOI: 10.1117/1.jpe.12.035501
|View full text |Cite
|
Sign up to set email alerts
|

P3HT:PCBM polymer solar cells from a didactic perspective

Abstract: Here, we studied the influence of pre-and post-thermal annealing on the performance of polymer:fullerene bulk heterojunction solar cells using the conventional architecture, comprising a conjugated polymer, namely, poly(3-hexylthiophene-2,5-diyl) (P3HT) and a fullerene derivative [6,6]-phenyl-C60-butyric acid methyl ester (PC 60 BM) as a photoactive layer. The nonannealed active layer device exhibited a power conversion efficiency of <1%, which was significantly lower than the pre-and post-annealed devices. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…The exciton dissociation efficiency ( η diss = J SC / J sat ) and charge collection efficiency ( η coll = J MPP / J sat ) were calculated at short circuit conditions and at the maximum power point, respectively. [ 57 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exciton dissociation efficiency ( η diss = J SC / J sat ) and charge collection efficiency ( η coll = J MPP / J sat ) were calculated at short circuit conditions and at the maximum power point, respectively. [ 57 ]…”
Section: Resultsmentioning
confidence: 99%
“…The exciton dissociation efficiency (𝜂 diss = J SC /J sat ) and charge collection efficiency (𝜂 coll = J MPP /J sat ) were calculated at short circuit conditions and at the maximum power point, respectively. [57] TPC measurements were performed to understand qualitative differences of the charge carrier transport properties, and the photocurrent decay was monitored after excitation with a 100 μs pulse, as shown in Figure 5a. The ratio between charge carriers extracted swiftly and those extracted after some delay time became smaller for increasing annealing temperatures.…”
Section: Charge Generation and Recombinationmentioning
confidence: 99%
“…In previous work, we presented a study on P3HT:PCBM-based organic solar cells, using several optoelectronic and spectroscopic measurements to investigate their photovoltaic properties. Photoluminescence (PL) studies demonstrated the highest film crystallinity for annealed films, which was confirmed by atomic force microscopy (AFM) [51]. An enhancement in crystallinity was primarily responsible for the improved photovoltaic characteristics upon annealing.…”
Section: Introductionmentioning
confidence: 77%
“…The device containing BP-3 can still significantly improve the UV stability in the harsh conditions of ISOS-L2. Electroluminescence imaging (ELI) was employed during the ISOS-L2 process to evaluate defect density for all layer stacks and the ability of charge carrier injection from the top electrode with the same set current of 20 mA, , and the original data are all shown in Figure S20. In contrast to a ZnO/BP-3-based device, a ZnO-based device with no modification layer of BP-3 exhibits a larger defect density and a similar brightness, indicating that the modification layer of BP-3 does not affect charge injection negatively while reducing the device’s internal defect density.…”
Section: Resultsmentioning
confidence: 99%